The I-35W bridge collapse: crimes of commission and omission resulting from the confluence of state processes and political-economic conditions - Schotter, Casey James (Critical criminology, 2013)
The Interstate-35 West Bridge collapse offers a unique case of state crime. First, it illuminates a new topical area in the state crime literature, public infrastructure. Second, it illustrates how the bridge collapse was not a discrete act (Tombs in State Crime 1(2):170-195, 2012), but rather the outcome of relationships between different social institutions. Specifically, it demonstrates how processes within a state, in confluence with the broader political economy, produced decisions (omissions) not to invest in infrastructure repair, take expert advice, and improve coordination between agencies. Simultaneously, these same processes resulted in deliberate actions (commissions) to invest in new infrastructure rather than in maintenance and repair of existing infrastructure, and to reduce both regulatory oversight and safety procedures. We provide a detailed overview of the bridge collapse, then utilizing Kauzlarich and Kramer’s (Crimes of the American nuclear state, Northeastern University Press, Boston, 1998) integrated theoretical framework, contextualize the causes of the collapse and highlight how state processes and political-economic conditions resulted in the simultaneous occurrence of crimes of omission and commission on the part of the state.